1985
DOI: 10.1002/j.2161-4296.1985.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Global Positioning System Operational Control System Accuracies

Abstract: In early 1985, an improved ground Operational Control System (OCS) will maintain the navigation service. Primary among the OCS improvements over past GPS navigation systems is a global network of ground antennas (to upload satellite navigation data) and tracking/monitor stations. In addition, a refined Kalman filter will continuously estimate the Global Positioning System (GPS) satellite ephemerides and clock phases and frequencies. Although the user-GPS interface remains unaltered, the accuracy of the GPS nav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…With the model thus verified, two of the filters derived from the SA waveforms were each used to perturb the pseudoranges. The results using the ARMA (2,2) are given in Figure 10 and the results using the AMRA (3,2) in Figure 11. The position errors again appear to be Gaussianly distributed.…”
Section: Signal Model Block Diagram and Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the model thus verified, two of the filters derived from the SA waveforms were each used to perturb the pseudoranges. The results using the ARMA (2,2) are given in Figure 10 and the results using the AMRA (3,2) in Figure 11. The position errors again appear to be Gaussianly distributed.…”
Section: Signal Model Block Diagram and Simulation Resultsmentioning
confidence: 99%
“…First, 27 ARMA and auto-regressive (AR) filter models of differing order were derived. The simplest acceptable signal generator filter was determined to be an ARMA filter model with three poles and two zeros, ARMA (3,2). To demonstrate this filter's acceptability, the autocorrelation function of the optimum filter output is given (Figure 3).…”
Section: Simple Analysis Of Sa Datamentioning
confidence: 99%
“…The length of baseline is about 185 metres and the altitude difference 64 metres. The short-term stability of GPS satellite clock is on the level of 10 x11 y10 x12 second (Bowen, 1985 ;Lutwak, 2001). We used the SNUR-2000 v. 2.2 as a RTK-GPS protocol which is optimized for low-rate data-link.…”
Section: E X P E R I M E N T a L R E S U L T Smentioning
confidence: 99%
“…Estimation of this y-bias parameter by the ICS dramatically improved the quality of the broadcast navigation messages. When the ICS was decommissioned in 1985, the broadcast user range error (URE) accuracy was better than 5 m 1 σ [19]. new predicted reference trajectories on a weekly basis.…”
Section: Initial Operationmentioning
confidence: 99%
“…A requirement was established for the OCS to provide a 1 URE of less than 6 m 10 h after upload. Initial comparisons of ICS and OCS indicated that this requirement could easily be met [19,21]. The Kalman filter used by the OCS can process up to six satellites in a single partition and uses 15 min pseudorange measurements smoothed using carrier-phase data.…”
Section: Operational Control Segment (Ocs)mentioning
confidence: 99%